سیرت النبیﷺ كی روشنی میں اسلامی معیشت كے اصولوں پر ایك تحقیقی جائزہ: A Research Review of the Principles of Islamic Economics in the Light of the Seerah of the Prophet ﷺ (Al-Qamar, 2024)
Islam is a comprehensive and complete way of life that provides guidance for all aspects of human existence, including religious, social, political, and economic affairs. The economic system, in particular, plays a vital role in shaping human life, as it directly affects social stability, justice, and overall well-being. Throughout history, economic injustice, exploitation, and inequality have remained major challenges for human societies. The Islamic economic system is founded on the principles of justice, balance, and moral responsibility. The practical and most authentic model of this system is found in the Seerah (life) of the Prophet Muhammad ﷺ. Through his teachings and actions, the Prophet ﷺ established an economic framework that aimed not merely at wealth accumulation, but at the preservation of human dignity, elimination of exploitation, and establishment of social justice.Before the advent of Islam, Arabian society was dominated by unjust economic practices such as usury (interest), fraud, hoarding, and exploitation of the poor. The Prophet ﷺ reformed this system by abolishing interest-based transactions, prohibiting dishonesty in trade, and promoting fairness and transparency in all financial dealings. These reforms laid the foundation of a moral and equitable economic order. After the establishment of the Islamic state in Madinah, the Prophet ﷺ practically implemented Islamic economic principles. The institution of Bayt al-Mal, the organized system of Zakat, regulation of markets, and protection of the rights of workers and traders clearly demonstrate that Islamic economics is not merely a theoretical concept, but a practical and applicable system.The primary objective of Islamic economics, as reflected in the Seerah of the Prophet ﷺ, is to maintain a balance between individual rights and collective welfare. Wealth is encouraged to circulate within society rather than being concentrated in the hands of a few. This balanced approach distinguishes Islamic economics from both capitalist and socialist systems. This research study aims to analyze the fundamental principles of Islamic economics in the light of the Seerah of the Prophet ﷺ and to highlight their relevance and effectiveness in addressing contemporary economic challenges such as poverty, inequality, and social injustice.
Keywords: Islamic Economics, Seerah of the Prophet ﷺ, Economic Justice, Prohibition of Interest, Social Welfare, Public Treasury